Management of Partially Edentulous Arches Using a Cast Metal Framework with Thermoplastic Denture Base Clasp-Like Extension on Anterior Abutment Teeth - A Case Report - MS Mithula; Smita Sara Manoj; Kurien Varghese; Radhika Ravi (Wolters Kluwer Medknow Publications, 2024)
Rehabilitation of partially edentulous arches with a cast partial denture is a commonly opted treatment modality where fixed prosthesis is not indicated. However, due to the aesthetic compromise of the various metal components when placed in the esthetic zone, different modifications have been considered for its fabrication. This case report describes a novel way of restoring partially edentulous arches with increased masticatory efficiency and good emergence profile without compromising the patient's esthetic desires. The report describes an aesthetic alternative using thermoplastic denture base clasp like extension for anterior abutment teeth while restoring the missing teeth with a cast partial denture.